Immigrants' spatial concentration: Region or locality attractiveness?. Issue 2 (2nd November 2021) - Viñuela, Ana
Abstract: The spatial concentration of immigrants across and within European countries is highly heterogeneous, tending to reinforce the internal spatial disparities within EU Member States and regions. Although European regional data show that the highest levels of foreign‐born population concentration correspond to those NUTS2 regions that contain a large city or metropolitan area, there are other place‐based determinants that might explain their attractiveness to immigrants. Using a comprehensive database at NUTS2 (regional) and LAU2 (local) levels for three large European countries in terms of immigrant population (Italy, Spain, and France), comparable results show how the relevance of these determinants depends on the country under analysis and the spatial unit chosen. This provides challenges for the design of a common future European policy addressing the unresolved demographic issues. Understanding the main regional and local factors of attraction to foreign‐born population within countries is crucial to explain the present spatial concentration patterns and anticipate future migration flows, especially in a context where immigrants are the fastest‐growing population group in those European countries. Nevertheless, there might be a trade‐off between the foreign‐born population alleviating the territorial ageing and depopulation issues and the search for spatial justice.